2022
DOI: 10.3390/diagnostics12123196
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Clostridioides Difficile Infection in Hospitalized Patients: What Changed during the Pandemic?

Abstract: (1) Background: Clostridioides difficile (C. difficile) and SARS-CoV-2 coronavirus represent significant health threats. Our study focused on the impact of concurrent infections on patient outcomes against the backdrop of changes imposed by the pandemic. (2) Materials and methods. We performed a retrospective analysis and included patients diagnosed with CDI who were admitted in our hospital before and during the pandemic. We compared patient exposure to risk factors for CDI in both groups and patient negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
2
4
3
Order By: Relevance
“…These findings are consistent with previous studies that have shown a higher incidence of CDI in COVID-19 patients compared to non-COVID-19 patients [ 13 , 14 ]. In a study by Boeriu et al, CDI incidence was significantly higher in COVID-19 patients, and the study identified several risk factors for CDI in COVID-19 patients, including advanced age, antibiotic use, and proton pump inhibitor (PPI) use [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with previous studies that have shown a higher incidence of CDI in COVID-19 patients compared to non-COVID-19 patients [ 13 , 14 ]. In a study by Boeriu et al, CDI incidence was significantly higher in COVID-19 patients, and the study identified several risk factors for CDI in COVID-19 patients, including advanced age, antibiotic use, and proton pump inhibitor (PPI) use [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Creatinine and CRP were singled out as independent predictors of a severe form of CDI and were attributed to mortality in patients with CDI before the start of the pandemic [ 43 ]. Although a negative impact of associated CDI and COVID-19 on patient outcomes was found [ 45 ], we did not find a difference in outcomes between COVID and non-–COVID HA-CDI patients. Our results are in concordance with those from Spain [ 25 ].…”
Section: Discussioncontrasting
confidence: 85%
“…The antibiotics most commonly associated with CDI are aminopenicillins, second and third-generation cephalosporins, fluoroquinolones, and clindamycin, which have seen an increase in their use in recent years [9]. The pathogenic power of CD is linked to its ability to produce two enterotoxins, TcdA and TcdB [13], which cause intestinal damage by activating an inflammatory cellular response with mild clinical manifestations ranging from asymptomatic colonization or mild and self-limiting diarrhea to more severe manifestations ranging from pseudomembranous colitis, which can lead to acute intestinal insufficiency with toxic megacolon, intestinal perforation, septic shock, disseminated intravascular coagulation (DIC), and death [14,15].…”
Section: General Characteristicsmentioning
confidence: 99%
“…CDI is a bacterial infection that primarily affects the colon and causes symptoms ranging from mild diarrhea to severe life-threatening conditions [14,15]. Clustering CDI involves grouping cases of the infection based on various factors to gain insights into its epidemiology, risk factors, and potential treatment approaches.…”
Section: Clostridioides Difficile Infection From the Perspective Of C...mentioning
confidence: 99%